DUKUNGAN SOSIAL, RESILIENSI DENGAN PEMBELAJARAN TATAP MUKA - Amanda Pasca Rini; Edy Purwanto; Firdaus Ananda (AMERTA Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2022)
Anxiety in students who take part in face-to-face learning needs attention because if left unchecked it can cause students to lose their academic potential. This study intends to determine the relationship between social support, resilience with face-to-face learning anxiety, the subjects in this study amounted to 633 students spread across 9 private schools in the city of Surabaya. The research data were taken using the social support scale (α=0.930), resilience (α=0.878), and anxiety (α=0.960). The results of data analysis using multiple regression showed that social support and resilience harmed anxiety simultaneously. Partially both variables also have a significant negative effect on anxiety. The results of this study implicate the importance of social support from the family environment and the importance of student resilience to be able to adapt when undergoing face-to-face learning so that anxiety does not occur so that academic performance decreases during face-to-face learning amid the covid-19 pandemic. Keywords: Social Support; Resilience; Worry; Face-to-face Learning